Study on Surface Modification and Properties of Filtration for Industrial Flue Gas Fine Particulate Matter Control and Low Carbon Emission. Issue 1 (September 2021) - Liu, Na; Chen, Xiangyun; Yu, Meifang
Abstract: In order to further improve the filtration performance of glass fiber filter material, the surface of glass fiber filter material was modified by preparation of nano-SiO2 and polytetrafluoroethylene (PTFE) emulsion compound finishing solution, and the permeability and filtration efficiency of the filter material before and after modification were tested. The results show that the filtration performance of the filter material is improved after surface modification. The content of SiO2 is 0.8g, the mass fraction of PTFE is 5%, the finishing time is 6h, the filtration efficiency of the modified filter material is 64.67%. At this time, the quality factor is the maximum, and meet the requirements of high efficiency and low resistance.